The Influence of Polyethylene Glycol Precipitation Methods on Yield and Purity of White Radish Peroxidase - Faizah, Nur Al; Giri-Rachman, Ernawati Arifin; Niloperbowo, Wardono (3BIO: Journal of Biological Science, Technology and Management, 2024)
Proteins are widely used in various industries as highly valued biotechnology products. One example is horseradish peroxidase isolated from horseradish (Armoracia rusticana) that used as enzyme label in immunochemistry. However, the cultivation of horseradish is limited to subtropical countries, making the dependency on horseradish peroxidase unsustainable for tropical countries. Numerous studies have explored alternative peroxidases, and white radish peroxidase isolated from Raphanus sativus L. has emerged as a promising candidate. In this study, white radish peroxidase is isolated using the polyethylene glycol (PEG) precipitation method which is widely used as a simple and cost-effective method. This study aims to evaluate the effectiveness of the one-step and two-step PEG precipitation method. The one-step PEG precipitation method used in this study was done by mixing the white radish juice with PEG 6000 30% (w/v), while the two-step method was done by mixing it with PEG 400 20% (w/v) and PEG 6000 30% (w/v) consecutively. This study compares the yield and recovery levels of total protein and white radish peroxidase, as well as the enzymatic specific activity of white radish peroxidase isolated both by the one-step PEG precipitation and the two-step PEG precipitation. The results indicate that both extraction methods yield the same level of white radish peroxidase. However, they differ in terms of purity. The two-step extraction method results in white radish peroxidase with higher purity, as evidenced by its specific activity towards the chromogen ABTS in the presence of H2O2.